From FPGA to Support Cloud to Cloud of FPGA: State of the Art. (5th December 2019) - Skhiri, Rym; Fresse, Virginie; Jamont, Jean Paul; Suffran, Benoit; Malek, Jihene
Abstract : Field Programmable Gate Array (FPGA) draws a significant attention from both industry and academia by accelerating computationally expensive applications and achieving low power consumption. FPGAs are interesting due to the flexibility and reconfigurabiltiy of their device. Cloud computing becomes a major trend towards infrastructure and computing resources dematerialization. It provides "unlimited" storage capacities and a large number of data and applications that make collaboration easier between multiple (not domain specific) designers. Many papers in the literature have surveyed Cloud and FPGA separately and, more precisely, their services and challenges. The acceleration of applications by FPGA and the unlimited capacities of the cloud are expected to be more and more pervasive. As more and more FPGA are being deployed in traditional cloud, it is appropriate to clarify what is the cloud FPGA and which drawbacks of using FPGA in local are resolved. We present a survey of the cloud FPGA works that have been proposed to exploit the advantages of using FPGA in the cloud. We classify these studies in three services to highlight their benefits and limitations. This survey aims at motivating further researches in cloud FPGA.